Antihyperuricemia of A Combination of Eleutherine bulbosa and Annona muricata Extracts on Reducing Uric Acid Levels in Hyperuricemia Mice - Azizah, Sarah; Hujjatusnaini, Noor; Indahsari, Lilin Ika Nur (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Increased uric acid levels in the blood have the potential to cause kidney problems and the formation of urate crystals in soft tissue if not treated properly. Standard treatments involving synthetic drugs, such as allopurinol, often cause side effects, making safer alternatives a necessity. This study aimed to investigate the effect of a combination of Eleutherine bulbosa and Annona muricataextracts on uric acid levels in hyperuricemic mice. This study used a posttest-only control-group design, with 28 male Balb/c mice induced with a high-purine diet, then given single and combination treatments at doses of 100, 200, and 300 mg/kg BW at a ratio of 1:2. Analysis using the Kruskal-Wallis and Mann-Whitney tests showed that the combination dose of 100 mg/kg body weight was most effective in reducing uric acid levels, with an average value of 2,7 mg/dL, while the single extract had no significant effect. At the cellular level, this combination works by inhibiting xantin oksidase (XO) enzyme activity, accelerating uric acid excretion through a diuretic mechanism, and reducing oxidative stress, which in turn helps protect kidney tissue from damage. Therefore, this combination has the potential to be a safe and effective natural antihyperuricemic agent.